What would Happen if UK Residents Stopped Having Babies?. Issue 2 (8th April 2016) - Timaeus, Ian
Abstract: The Year 6 children of Milwards Primary School ask: If current UK residents stopped having babies, how long would it take for the human population to drop to zero? What would happen if UK residents stopped having babies? Demographer Ian Timæus offers some projections